1976
DOI: 10.1146/annurev.bi.45.070176.001245
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Aspects of Glycoprotein Structure

Abstract: Glycoproteins have a wide distribution in nature and serve a vast number of functions. There are glycoprotein enzymes and hormones; glycoproteins are found in blood and secretions, in cell membranes, and in connective tissue. Of all the biologically occurring macromolecules the glycoproteins, which consist of carbohydrate moieties convalently linked to a polypeptide backbone, represent the most diverse group, ranging from substances in which the carbohydrate component represents less than 1% of the total weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
262
2
2

Year Published

1978
1978
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 756 publications
(278 citation statements)
references
References 19 publications
(23 reference statements)
12
262
2
2
Order By: Relevance
“…To eliminate the possibility of an additional O-linked glycosylation, which had been found in another mouse IgA at the position corresponding to Ser H223 [23], as the cause of the remaining discrepancy between the molecular weight of the recombinant and the Nglycosidase treated Fat, fragment, an amino sugar analysis was carried out as described in section 2. Glucosamine, but no galactosamine was detected, indicating the absence of O-linked glycosylation [24,25]. Therefore, pepsin cleavage must give rise to a larger heavy chain fragment than visible in the electron density.…”
Section: Resultsmentioning
confidence: 96%
“…To eliminate the possibility of an additional O-linked glycosylation, which had been found in another mouse IgA at the position corresponding to Ser H223 [23], as the cause of the remaining discrepancy between the molecular weight of the recombinant and the Nglycosidase treated Fat, fragment, an amino sugar analysis was carried out as described in section 2. Glucosamine, but no galactosamine was detected, indicating the absence of O-linked glycosylation [24,25]. Therefore, pepsin cleavage must give rise to a larger heavy chain fragment than visible in the electron density.…”
Section: Resultsmentioning
confidence: 96%
“…Wieder et al (33) drew a different conclusion; they found I-J k determinants on in vitro translated proteins presumably devoid of carbohydrate. Terminal mannosyl residues occur on simple, or high-mannose types of oligosaccharides (34). Neuraminidase treatment increased T cell I-J k expression; this probably does not imply that sialic acid residues are attached to the nonreducing ends of some high-mannose, I-Jk-bearing carbohydrate chains.…”
Section: Discussionmentioning
confidence: 96%
“…Neuraminidase treatment increased T cell I-J k expression; this probably does not imply that sialic acid residues are attached to the nonreducing ends of some high-mannose, I-Jk-bearing carbohydrate chains. Only complex type carbohydrate chains have to date borne terminal sialic acid residues (34). Furthermore, it seems unlikely that mannosyl groups themselves form the I-J k epitope, since these residues are so prevalent on mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…The two main families are those having oligosaccharide chains linked N-glycosidically from N-acetyl-D-glucosamine to the amide nitrogen of asparagine and those possessing oligosaccharide chains O-glycosidically linked from N-acetyl-D-galactosamine (GaINAc)' to the hydroxyl groups of serine and/or threonine (22,28,35,36,72). The biosynthesis of Nlinked glycoproteins is currently considered to be a single pathway involving the assembly ofa lipid linked oligosaccharide (1,41,42), the en bloc transfer of the oligosaccharide from the lipid carrier to the nascent peptide chain (31,32,55), the processing of the oligosaccharide chains by glycosidases (12,18,24,27,38,(63)(64)(65)(66) and the addition of terminal sugars by glycosyltransferases (5,44,57).…”
mentioning
confidence: 99%